Online harassment of Japanese celebrities and influencers - Takano, Masanori; Taka, Fumiaki; Ogiue, Chiki; Nagata, Natsuki (Frontiers in Psychology, 2024)
Famous people, such as celebrities and influencers, are harassed online on a daily basis.Online harassment mentally disturbs them and negatively affects society. However, limited studies have been conducted on the online harassment victimization of famous people, and its effects remain unclear. We surveyed Japanese famous people (N = 213), who were influential people who appeared on television and other traditional media and on social media, regarding online harassment victimization, emotional injury, and action against offenders and revealed that various forms of online harassment are prevalent. Some victims used the anti-harassment functions provided by weblogs and social media systems (e.g., blocking/muting/reporting offender accounts and closing comment forms), talked about their victimization to close people, and contacted relevant authorities to take legal action (talent agencies, legal consultants, and police). By contrast, some victims felt compelled to accept harassment and did not initiate action for offenses. We propose several approaches to support victims, inhibit online harassment, and educate people.Our findings help that platforms establish support systems against online harassment.